Trust and Stakeholder Theory: Trustworthiness in the Organisation–Stakeholder Relationship - Greenwood, Michelle (Journal of business ethics, 2010)
Trust is a fundamental aspect of the moral treatment of stakeholders within the organization–stakeholder relationship. Stakeholders trust the organization to return benefit or protections from harm commensurate with their contributions or stakes. However, in many situations, the firm holds greater power than the stakeholder and therefore cannot necessarily be trusted to return the aforementioned duty to the stakeholder. Stakeholders must therefore rely on the trustworthiness of the organization to fulfill obligations in accordance to Phillips’ principle of fairness (Business Ethics Quarterly 7(1), 1997, 51–66), particularly where low-power stakeholders may not be fully consenting (Van Buren III, Business Ethics Quarterly 11(3), 2001, 481–499). The construct of organizational trustworthiness developed herewith is presented as a possible solution to the problem of unfairness in organization–stakeholder relations. While organizational trustworthiness does not create an ethical obligation where none existed before, stakeholders who lack power will likely be treated fairly when organizational trustworthiness is present.